The Influence of Knowledge About HIV/AIDS on Adolescents' Willingness to Play an Active Role in the Youth Information and Counseling Center (PIK-R) Program - -, Nurlindawati; widyawati, Sri (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2024)
Adolescence is a productive age that is very vulnerable to contracting HIV-AIDS, because when teenagers experience high sexual urges and are always looking for information about sex, and the knowledge and knowledge related to reproductive health that they obtain is very lacking. Many teenagers prefer to look for various sources of information that they can obtain, such as accessing adult sites on the internet, trying to masturbate, making out or even having sex with their girlfriend. The PIK-R program is a program of, by and for teenagers which was created as an effort to reduce the number of HIV/AIDS cases. This research aims to see the willingness or interest of teenagers to play an active role in the PIK-R program before and after being given education about PIK-R. This research uses a Quasi Experimental method without a control group with a One Group Pre-Test and Post-Test approach. Data after research is primary data collected using research instruments in the form of questionnaires which will be announced to respondents before and education is provided. The analysis used is Paired Samples T-Test. The sample in this study was 100 class XII students majoring in Office and Accounting at one of the vocational schools in Jakarta with inclusion and exclusion criteria. The research results obtained were that the majority of students' knowledge about PIK-R increased, had the perspective that PIK-R was important, agreed that PIK-R was held at school, and were willing to actively participate in the PIK-R program after being given education about PIK-R. The conclusion is a person's willingness to accept and apply something new, the need for introduction and learning to be remembered, then understood and then applied.